OPTIMIZING LAW ENFORCEMENT THROUGH A RESTORATIVE JUSTICE APPROACH FOR POST-PANDEMIC COMMUNITY RECOVERY IN BOJONEGORO REGENCY, INDONESIA - Aminatul Mukaromah, Lisa; Anam, Khurul (Kanun Jurnal Ilmu Hukum, 2024)
The economic instability following the Covid-19 pandemic has led to a potential increase in criminal activity within society. Addressing this challenge requires innovative approaches to law enforcement. This paper examines the application of restorative justice principles in restoring the economy of the community in Bojonegoro Regency post-pandemic. Utilizing normative-empirical research methods, this study assesses the progressive impact of restorative justice in this context. The findings indicate that restorative justice in Bojonegoro Regency has successfully shifted away from a punitive justice paradigm, leading to positive economic outcomes for the community. However, the lack of supervision remains a critical issue that needs to be addressed to enhance the implementation and further improve the economic recovery process. This case serves as a valuable example for the effective implementation of restorative justice within the Indonesian context.